Fun Holiday with English: Pengenalan Literasi Bahasa Inggris Bagi Siswa SD di Kota Lhokseumawe - Mardhiah, Ainol; Muna, Hayatul; Hayati, Ulfi (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service program titled "FUN HOLIDAY WITH ENGLISH: Introducing English Literacy to Elementary School Students in Lhokseumawe" was implemented as an initiative to provide an alternative educational activity during the school holidays. The program aimed to enhance English literacy in an interactive and enjoyable manner while also reducing excessive smartphone use during the holidays. Students from Universitas Bumi Persada and IAIN Lhokseumawe applied the pedagogical theories and knowledge they had acquired to design an English teaching program for elementary students using a service-learning approach. The program was carried out in collaboration with Universitas Bumi Persada, IAIN Lhokseumawe, STIT Syamsuddhuha and the Lhokseumawe City Library and Archives Department, taking place over four sessions at the Lhokseumawe Public Library. The results indicate that the children improved their mastery of basic vocabulary, with 80 percent of participants able to recall and use the vocabulary taught. The university students also gained valuable experience in classroom management, adapting teaching methods, and engaging in reflective practice. Furthermore, the children developed a greater interest in learning English and utilizing library resources, leading to positive impacts on the local community. This cross-institutional collaboration demonstrates the effectiveness of community service programs in supporting literacy and skill development.